Expert consensus on the usability of the SLC3DM model a fuzzy delphi method application - Faiezah Shamsuddin (Tanjong Malim, 2024)
Expert consensus on the usability of the SLC3DM model a fuzzy delphi method application by Faiezah Shamsuddin